Training on monitoring side effects of diabetes mellitus drugs for Persadia members - Farroh Bintang Sabiti; Nur Anna Chalimah Sa’dyah (Universitas Muhammadiyah Magelang, 2022)
People with diabetes are often unaware of the side effects of the medications they take, including both oral diabetic medications and insulin. This program is provided in an effort to empower the Indonesian Diabetes Association (Persadia) Semarang City Branch's training on monitoring pharmacological side effects in diabetes mellitus patients who are self-isolating. It is hoped that by participating in this activity, drug compliance would improve, the death rate from diabetes will reduce, and the complexity of comorbidities will be avoided. The results of implementing this program, namely monitoring the side effects of taking diabetic mellitus drugs in Persadia members, can raise understanding of side effect symptoms, resulting in increased adherence to diabetes drug use and better blood sugar control.